Long‐term renal tubular damage in intrauterine growth‐restricted rats. Issue 6 (19th June 2018) - Murano, Yayoi; Shoji, Hiromichi; Hara, Taichi; Ikeda, Naho; Endo, Amane; Nishizaki, Naoto; Shimizu, Toshiaki
Abstract: Background: Intrauterine growth restriction (IUGR) has been shown to be associated with increased risk of renal disease or hypertension in later life. Glomerular dysfunction, however, has mainly been reported, and limited information is available to link IUGR with renal tubular damage. The aim of this study was therefore to investigate urinary markers of tubular damage in a rat model of IUGR induced by bilateral uterine artery ligation. Methods: Pregnant Sprague–Dawley rats underwent bilateral uterine artery ligation, while the control group underwent sham surgery. Results: Birthweight was reduced, and urinary β2‐microglobulin (β2‐MG)‐, cystatin C (Cys‐C)‐, and calbindin‐to‐creatinine ratios were significantly higher at weeks 4 and 8 in the IUGR group compared with the control group. These urinary markers were not significantly different at week 16 between the two groups. Increased excretion of urinary β2‐MG, Cys‐C, and calbindin was observed in IUGR rats at ≥8 weeks of age. Conclusion: Children born with IUGR are at increased risk for renal tubular damage.